Determinants of Return-to-Work among Employees Absent Due to Mental Health Problems - St-Arnaud, Louise; Bourbonnais, Renée; Saint-Jean, Micheline; Rhéaume, Jacques (Relations industrielles / Industrial Relations, 2007)
The contribution of work in the occurrence of mental health problems prompts us to question the conditions which favour a successful return to work. The goals of this study are to describe the profile of workers who have been absent due to a mental health problem and to compare those who returned to those who did not, and those for whom there was resolution or non resolution of their health problem. This study among public sector employees was cross-sectional. Data was collected using mailed questionnaires and analyses were performed for 1850 respondents. The results show a significant difference between those who were back at work and those who were not, based on the cause they reported for their absence from work. Improved working conditions accompanying return to work may be a major determinant of health recovery and successful return to work, and ensure job retention.